THE OPTIMIZING THE EXTRACTION PROCESS OF BIOLOGICALLY ACTIVE SUBSTANCES OBTAINED FROM DANDELION LEAVES (TARAXACUM OFFICINALE WIGG) - Kosogolova, Ludmila; Polishchuk, Bogdana; Kryvutenko, Iryna; Yablonska, Kateryna; Romanova, Zoriana; Hurska, Olena (Proceedings of National Aviation University, 2017)
Purpose: to optimize the process of separation of biologically active substances from medicinal dandelion leaves. Methods: Different methods for the selection of biologically active substances from the medicinal dandelion (Taraxacum oficinale Wigg.), Including ultrasound treatment, were performed at 4, 5 and 6 W/m2 at 5, 10, 15, 20, 25 minutes. Results: The aquatic extracts of dandelion officinalis (Taraxacum officinale Wigg) have been obtained for selecting biologically active substances, namely vitamin C. The optimal conditions for the extraction process are chosen: the ratio of raw material:extractant 1:20, extraction time - 30 minutes, temperature - 25 ° C . The extraction was performed with distilled water. Discussion: It was investigated that the extraction of medicinal plant material results in the diffusion of biologically active substances from the internal structures of the material particle. This process has its own peculiarities. First of all, the presence of porous septum, intercellular space and cellular movements reduces the diffusion rate. Secondly, in the porous partition, only those substances whose particles do not exceed pore sizes can penetrate. Also, the phenomenon of desorption observed in the cell after penetration of the extractant into it is characteristic. The optimal conditions for the extraction of biologically active substances from medicinal dandelion (Taraxacum officinale Wigg) were determined: - extractant water; - ratio of extractive raw material (1:20); - time of infusion 30 minutes; - temperature 25 °C. Ultrasonic fluctuations optimize the process of vitamin C extraction from dandelion leaf extracts and as a result, it has been found that the highest yield of ascorbic acid in extracts treatment by ultrasound for 25 minutes with a power of 6 W/m2 and is 0.077 mg per 100 g of product.